INTEGRATING HYPERTONIA REHABILITATION, INTRAORAL REHABILITATION, AND ANXIETY MANAGEMENT FOR COMPREHENSIVE PATIENT CARE- PART.3 –DIAGNOSIS AND TREATMENT PLAN COMPLEX ORAL REHABILITATION - Ștefan Lucian Burlea; Ovidiu Stamatin; Mihaela Salceanu; Violina Budu; Vlad Proca; Bogdan Petru Bulancea; Tudor Hamburda; Doriana Agop Forna; Maria Antonela Beldiman (Romanian Journal of Oral Rehabilitation)
The masticatory apparatus, which includes the jaw and related muscles, can suffer from dysfunctions like muscle rigidity. This condition is often treated with muscle relaxants, medications that ease muscle tension, with Botulinum toxin (Botox) being one of the most effective options. Clinical cases have demonstrated that Botox can significantly alleviate symptoms of temporomandibular joint disorders, characterized by pain and restricted jaw movement.